The Implementation of Lineage Determination Methods in Illegal Marriages based on Wahbah Al-Zuhaily in the Determination of Banjarbaru Religious Court No. 80/Pdt.P/2017/PA.Bjb - Hasanudin Hasanudin; Fatimatuzzahro Fatimatuzzahro (Al Ahkam, 2022)
This article discusses the method of determining lineage in fasid marriages according to Wahbah al-Zuhaily and its application in the Determination of the Banjarbaru PA No. 80/Pdt.P/2017/PA.Bjb regarding the judge's legal considerations in determining the case. Lineage is a family relationship that determines the origin of a child and causes civil law consequences, including inheritance rights, livelihood rights, and so on. Determination of lineage is very important because it is directly related to the family structure. Methods of determining lineage also vary, including through legal or fasid marriage, confession, and proof. In Islam, it is known that marriages that do not meet the legal requirements of marriage are known as fasid marriages. Fasid marriage is not legal. Has no legal status before the occurrence of intercourse. A child from a fasid lineage marriage is still dependent on his father if he meets the requirements in terms of the husband's ability to get pregnant or not, in terms of whether he has a husband or not, and from the minimum period of pregnancy whether he fulfills it or not. The istinbat method used by Wahbah al-Zuhaily is istislah, which is to protect the interests of the child so that his rights are protected. As for the application of Islamic marriage law in court stipulation no. 80/Pdt.P/2017/PA.Bjb the judge is in accordance with and refers to Wahbah al-Zuhaily's opinion as a legal consideration in determining the origin of the lineage of children in fasid marriages through certain conditions that have been exceeded by the applicants.